Use of synchrotron X-rays for direct observation of wear damage in optically-opaque contacts by means of CT imaging and X-ray diffraction - Aleksejev, J; Williamson, M; Huber, JE; Magdysyuk, OV; Michalik, S; Marrow, TJ (Elsevier, 2022)
In a simulated in-situ experiment annular contacts of 6082-T6 aluminium alloy were first exposed to various degrees of fretting wear, before synchrotron X-ray CT and diffraction were applied to examine the extent and development of wear damage. The wear volumes measured and development of the wear rate were consistent with the mathematical wear model of Fillot, Iordanoff & Berthier. Thickness and porosity of the worn zone were measured and the contact area between wearing elements estimated. Developments of residual strain and tribologically transformed structure were investigated through X-ray diffraction. This study demonstrates, for the first time, the value and viability of observing and quantifying wear through combination of X-ray CT and diffraction opening a path towards in-situ observations of wear.